Development of an ergonomic infant seat with restraint system for use inan aircraft - Kamarbhari, Syakirah; Abdul Aziz, Faieza; Mohd Yusuff, Rosnah (Trans Tech Publications, 2014)
A restraint system to holdan infant between 0 – 24 monthsold ona commercial passenger aircraft has not been improvedsince the early development of the aviation industry. The ergonomic featureof the seat that fits the infant was not extensively studied compared to the development of the seat with restraint devices for adult passenger. The objective of this paper is to review the current regulations regarding restraint devices for infants in an aircraft. It also attempts to explore the ergonomics of current and new technology of infant seat with restraint system.